Understanding and applying the RE-AIM framework: Clarifications and resources. Issue 1 (14th May 2021) - Holtrop, Jodi Summers; Estabrooks, Paul A.; Gaglio, Bridget; Harden, Samantha M.; Kessler, Rodger S.; King, Diane K.; Kwan, Bethany M.; Ory, Marcia G.; Rabin, Borsika A.; Shelton, Rachel C.; Glasgow, Russell E.
Abstract: Introduction: Understanding, categorizing, and using implementation science theories, models, and frameworks is a complex undertaking. The issues involved are even more challenging given the large number of frameworks and that some of them evolve significantly over time. As a consequence, researchers and practitioners may be unintentionally mischaracterizing frameworks or basing actions and conclusions on outdated versions of a framework. Methods: This paper addresses how the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework has been described, summarizes how the model has evolved over time, and identifies and corrects several misconceptions. Results: We address 13 specific areas where misconceptions have been noted concerning the use of RE-AIM and summarize current guidance on these issues. We also discuss key changes to RE-AIM over the past 20 years, including the evolution to Pragmatic Robust Implementation and Sustainability Model, and provide resources for potential users to guide application of the framework. Conclusions: RE-AIM and many other theories and frameworks have evolved, been misunderstood, and sometimes been misapplied. To some degree, this is inevitable, but we conclude by suggesting some actions that reviewers, framework developers, and those selecting or applying frameworks can do to prevent or alleviate these problems.